LAW ENFORCEMENT IN THE SETTLEMENT OF HEALTH DISPUTES THROUGH MEDIATION EFFORTS - Priyambodo, Agus (Awang Long Law Review, 2021)
The legal relationship between medical personnel and patients in carrying out their services as health workers is often passed by an incident where health workers ignore a patient's right until a problem or dispute arises. Mediation is one form of alternative dispute resolution (ADR) or alternative dispute resolution outside the court. This mediation is considered to be more beneficial for the parties because the mediator does not have the authority to decide, but only acts as an intermediary for an agreement made by the parties. The advantage of using mediation channels is that the procedure is simple, effective, inexpensive, the decision is still under the control (control) of the disputing parties. Regulations regarding medical malpractice dispute resolution through mediation are regulated in Law Number 36 Year 2009 Article 29 concerning Health "In the event that a health worker is suspected of negligence in carrying out his profession, the negligence must be resolved first through mediation".